The Role o Students’ Critical Thinking and Interpersonal Intelligence in Understanding The Concept of Science (Universitas Negeri Semarang, 2018)
This research aims to: (1) analyze the role of critical thinking of grade V students in Science learning using Cooperative Problem Based Learning model, (2) analyze the role of interpersonal intelligence of grade V students in Science learning using Cooperative Problem Based Learning model as reflected on the Science learning outcome, (3) and acknowledge the influence of critical thinking and interpersonal intelligence of grade V students on their learning outcomes in Science learning using Cooperative Problem Based Learning model. This research used mixed method concurrent embedded. The samples of this research were the students of grade V of Tunon 1 and Tunon 2 State Elementary Schools. The data were taken through observation, test, interview and documentation. The results showed that the critical thinking of grade V students in Science learning using cooperative problem based learning model gave positive and significant impact of 36.3% on the outcome of Science learning. Students with high critical thinking skill tend to have high learning outcomes, students with moderate critical thinking skill tend to have moderate learning outcomes, and students with low critical thinking skill tend to have low learning outcomes. Students who have interpersonal intelligence skill in Science learning using cooperative problem based learning model gave positive and significant impact of 34.0% on the outcome of Science learming. Students with high interpersonal intelligence skill tend to have high learning outcomes, students with moderate interpersonal intelligence skill tend to have moderate learning outcomes, and students with low interpersonal intelligence skill tend to have low learning outcomes. Grade V students’ critical thinking skill and interpersonal intelligence together affected their learning outcomes of Science by 53.7%, and the remaining was 100% - 53.7% = 46.3%. Both the critical thinking skill and interpersonal intelligence were complementary abilities in achieving optimal learning outcomes of Science.